Gridded habitat ranges of Atlantic salmon (Salmo salar) gathered from historical sources - Yamuna Henke; Ronja Hegemann; Martin Offermann; Michael Hein; Johannes Rabiger-Völlmer; Christoph Zielhofer (PANGAEA, 2025)
Until the middle of the 20th century, the Atlantic salmon (Salmo salar) was an important migratory fish species in the Elbe River. Its decline and disappearance from the river and its tributaries during the last century can be seen as an indication of changes in the river habitat. Here we provide historical habitat ranges of Atlantic salmon mapped out of catch records gathered from historical sources and recent data in a simplified presence/absence approach for the Elbe River system. We used a standardized 16 km^2 grid approach created for data synthesis within SPP 2361 "On the Way to the Fluvial Anthroposphere" for mapping habitat ranges. Time slices for presence data are 1300-1500, 1501-1600, 1601-1700, 1701-1800, 1801-1850, 1851-1900, 1901-1947 and 1996-2021. Between 1947 and 1995 the Salmon was considered extinct in the Elbe River system.